Perlindungan Hukum Anak Korban Kekerasan Seksual dari Reviktimisasi dalam Sistem Peradilan Pidana - Indriastuti Yustiningsih (Lex Renaissance, 2020)
Child victims of sexual violence who undergo the criminal justice process still experience re-victimization when giving their testimony in court, child victims must remember and recount the chronology of the sexual violence they experienced, where it will cause psychological trauma that will take longer to heal and will affect the victim’s future . Departing from this perspective, this study intends to examine the efforts to prevent the victimization of child sexual violence victims in the criminal justice system in Indonesia. This is an empirical research with an empirical juridical approach by examining how the law works in the society. This research concludes that in order to prevent the re-victimization of child victims of sexual violence in the criminal justice system, a legal policy is needed by making changes to the criminal procedural law. The provisions contained in Article 58 paragraph (3) letter (a)  of Law Number 11 of 2012 on the Juvenile Criminal Justice System for Children can be applied as a basis for examining child victims since the beginning of the judicial process, in which electrocnic recording should be made during the investigation stage, oath-taking and making a Police Investigation Report (BAP), and it can be used as an admissible evidence in the argumentation, so that it is sufficient for the victim to provide information only at the investigation stage.